Graphic Adaptive Transformation Of Islamic Motifs A Case Study Of Kedah Traditional House - A. Bakar, Abdelaziz Eisa (2000)
This study attempts to identify, analyse and transform selected motifs found in several traditional houses in Kedah. The aim of this study is to explore the potential of trans forming local Islamic motifs into a digital format, enabling them to be used widely in other fields of design. This study is qualitative in nature. It began with the identification of architectural Islamic motifs, which followed by drawing and computing processes. In addition, certain procedures were carried to modify the motifs' designs. The study revealed the unity concept and understanding of Islamic art and its diversity that related to local factors. It found that the geometrical shapes and calligraphic forms were not widely used in Malaysia. Furthermore the calligraphic motifs needed certain ways of modification and changes. It is hoped that this study would encourage more Muslim artists and designers in Malaysia to use Malaysian-based Islamic motif in their work.